2005
DOI: 10.1177/104990910502200508
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual well-being as a dimension of quality of life for patients with advanced cancer and AIDS and their family caregivers: Results of a longitudinal study

Abstract: Based on a longitudinal, quality-of-life study, this article presents pilot data regarding the spiritual well-being of patients with advanced cancer or AIDS and their family caregivers. Data include similarities and differences between the patient and caregiver populations and patient/family caregiver dyads as well as trends with regard to changes in spiritual well-being during the illness and dying process. The reliability of the Spiritual Well-Being Scale was examined for patient and caregiver groups, as was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
(30 reference statements)
0
17
0
1
Order By: Relevance
“…[16][17][18][19] Further studies are needed to compare differences in quality of life for AIDS and cancer caregivers. Interestingly, based on the Spiritual Well-being Scale (SWBS), 42 which was also administered in this current study and is discussed in another article, 43 AIDS caregivers were found to have lower spiritual well-being than cancer caregivers. The use of unidimensional instruments to measure a construct, such as spiritual well-being, may lead to different results when compared to multidimensional instruments such as the QLS that measured spiritual well-being as a subscale.…”
Section: Discussionmentioning
confidence: 97%
“…[16][17][18][19] Further studies are needed to compare differences in quality of life for AIDS and cancer caregivers. Interestingly, based on the Spiritual Well-being Scale (SWBS), 42 which was also administered in this current study and is discussed in another article, 43 AIDS caregivers were found to have lower spiritual well-being than cancer caregivers. The use of unidimensional instruments to measure a construct, such as spiritual well-being, may lead to different results when compared to multidimensional instruments such as the QLS that measured spiritual well-being as a subscale.…”
Section: Discussionmentioning
confidence: 97%
“…[19][20][21][22] Caregivers may use spirituality as a way of coping, to lower their level of depression. 23,24 Caregivers who had spiritual support through the trajectory of illness had better well-being. Those that scored higher on spirituality had lower stress.…”
Section: Spiritual Healthmentioning
confidence: 97%
“…Integration of transcendence, whether in the form of polytheism (or pantheism), monotheism, or atheism, is also a function of culture (Johnson, Elbert-Avila, & Tulsky, 2005). It has been suggested that people with cancer have increased spiritual needs because of the existential stresses of living with a potentially life-threatening disease (Post-White, 2003; Sherman et al, 2005; Taylor, 2003). …”
Section: Introductionmentioning
confidence: 99%